2018
DOI: 10.1177/0117196818780087
|View full text |Cite
|
Sign up to set email alerts
|

“The lottery of my life”: Migration trajectories and the production of precarity among Bangladeshi migrant workers in Singapore's construction industry

Abstract: Within the scholarship on precarity, low-waged contract-based migrants are recognized as centrally implicated in precarious employment conditions at the bottom of neoliberal capitalist labor markets. Precarity as a socially corrosive condition stems from both the multiple insecurities of the workplace as disposable labor, and a sense of deportability as migrant subjects with marginal socio-legal status in the host society. Our study of Bangladeshi construction workers in Singapore contributes to refining under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Urban areas in North America, South America, Europe, the Middle East, Asia and Australia [79] experienced more hazardous heat stress nights than rural territories as a result of a higher current day heat stress during 2000-2016. In Korea, a significant positive correlation between an increase in temperature and local population growth has also been reported, which indicated that urbanization had a significant contribution to the temperature increase in 40 Korean cities during 1975-2005 [80][81][82]. In the next section, we consider findings from the literature on how climate change is linked to conflicts.…”
Section: Urbanization and Displacement Risksmentioning
confidence: 89%
“…Urban areas in North America, South America, Europe, the Middle East, Asia and Australia [79] experienced more hazardous heat stress nights than rural territories as a result of a higher current day heat stress during 2000-2016. In Korea, a significant positive correlation between an increase in temperature and local population growth has also been reported, which indicated that urbanization had a significant contribution to the temperature increase in 40 Korean cities during 1975-2005 [80][81][82]. In the next section, we consider findings from the literature on how climate change is linked to conflicts.…”
Section: Urbanization and Displacement Risksmentioning
confidence: 89%
“…Migrant workers in Southeast Asia are both domestic (mainly rural-to-urban) and international (mostly poor-to-rich country), and are highly heterogenous. For example, documented migrant workers in Singapore are generally semi-skilled and better paid than both documented and undocumented migrants from Laos and Myanmar working in Thailand (Derks 2010;Baey and Yeoh 2018). But for most, basic pay alone is not sufficient to make the migrant journey worthwhile and overtime is essential.…”
Section: Migrant Livelihood Pathways Rupture and The Covid-19 Pandemicmentioning
confidence: 99%
“…State regulations in Singapore have also created the conditions for extreme labour exploitation and a migrant workforce with few civil liberties and rights. Singapore has a two-tier system for skilled and unskilled migrant workers (Baey & Yeoh 2018). The regime has been criticised for creating hyper-precarious conditions by allowing employers and the state to collude over punitive debt-bondage arrangements (Platt et al 2017), as well as the regulation of the residence and reproductive rights of migrants (Huang & Yeoh 1998).…”
Section: Migration For Domestic Workmentioning
confidence: 99%